Mycophenolate mofetil after tacrolimus for refractory clinically amyopathic dermatomyositis: a case report - Ling, Gui-Chen; Su, Chang; Guo, Ying-Ao; Qiu, Xia; Liu, Jia-Wei; Xiao, Min; Xiao, Yu-Ya; Yang, Shuo; Zhang, Jian-Yong; Xie, Jing-Jing (Frontiers in Pharmacology, 2024)
Dermatomyositis (DM) positive for anti-melanoma differentiation-associated gene 5 (MDA5) antibodies, mainly when linked with rapidly progressive interstitial lung disease (RP-ILD), is considered a refractory disease. Our report describes a critical case of clinically amyopathic dermatomyositis (CADM) with RP-ILD that tested positive for both anti-MDA5 and anti-Ro-52 antibodies. The patient showed a limited response to a combined therapy regimen of prednisone, iguratimod, and tacrolimus. However, after adjunct therapy with mycophenolate mofetil (MMF), the patient's condition was controlled, his serum KL-6 levels decreased, and anti-MDA5 antibodies became negative. During the 68-week follow-up, the patient's condition remained stable, with a satisfactory quality of life. This report also discusses the potential role of inflammatory cytokines in the pathophysiology of CADM and RP-ILD. Further research is required to confirm these results and investigate the application of MMF in maintenance therapy for CADM-associated RP-ILD.